Efecto del fruto de Solanum sessiliflorum Dunal “cocona” en hiperlipidemia inducida en Mus musculus var. swiss - Tocto Chaquila, Yanitza Fiorella (2017)
The objective of this research was to determine the hypolipidemic activity of the fruit of Solanum sessiliflorum Dunal “cocona” in a model of acute hyperlipidemia induced by triton. Mus musculus var. swiss males as experimental animals. We worked with four groups of mice; the white group received distilled water orally and saline intraperitoneally, the controlgroup received distilled water orally and intraperitoneally triton, the problem group I received orally 0.05g/100g Solanum sessiliflorum Dunal extract intraperitoneally and triton and the problem group II received orally 0.2g/100g extract of Solanum sessiliflorum Dunal and triton intraperitoneally. After 24 hours of administering the treatments were performed measurements of serum cholesterol and triglycerides. Mean levels of cholesterol (mg/dL) were: 100.47±19.84 (white), 160.9±52.66 (control), 102.83±26.15 (Problem I) and 133.83±39.48 (Problem II). Average levels of triglycerides (mg/dL) were: 99.5±9.99 (white), 119.4±16.4 (control), 116±15.28 (Problem I) and 103.33±20.05 (Problem II). We found significant reductions (p <0.05), concentrations of both colesterol of problem group I in relation to those obtained in the group treated only with Triton, also it is substantially decreased triglyceride levels, but not statistically significant